Ответ:
1. a) x₁= 6; x₂= -3;
б)
Пошаговое объяснение:
1. a) |2*x-3|-14= -5; |2*x-3|= 9; 2*x-3=9; x₁= 6; 2*x-3= -9; x₂=-3;
б) -7/10*(0,6х+2/5)+0,3*(3/5х+0,4)=0; -21/50х-14/50+9/50х+6/50=0; 12/50х= -4/25; х= -2/3
2. в= 2-3= -1
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
1. a) x₁= 6; x₂= -3;
б)
Пошаговое объяснение:
1. a) |2*x-3|-14= -5; |2*x-3|= 9; 2*x-3=9; x₁= 6; 2*x-3= -9; x₂=-3;
б) -7/10*(0,6х+2/5)+0,3*(3/5х+0,4)=0; -21/50х-14/50+9/50х+6/50=0; 12/50х= -4/25; х= -2/3
2. в= 2-3= -1